Kualitas Alumni Pondok Pesantren Memimpin Lembaga Pendidikan Formal Sebagai SDM Unggul di Era Digital - Iskandar, Iskandar; Sunhaji, Sunhaji (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the role and quality of Islamic boarding school alumni in leading formal educational institutions amid the challenges of the digital era, with a focus on leadership competencies, digital skills, and religious character as superior human resources. The method used is a literature review with thematic analysis of relevant local literature published in the period 2021–2024 to identify factors that influence the success of Islamic boarding school alumni in educational leadership. The results of the study show that Islamic boarding school alumni have a strong foundation in traditional Islamic boarding school values, such as discipline, work ethic, moral responsibility, and prophetic leadership, which support their effectiveness in leading formal educational institutions. However, these values need to be reinforced with digital literacy, modern educational management skills, and professional networks in order to respond to the changes and demands of the digital era. Based on these findings, this study recommends the integration of digital literacy into the pesantren curriculum, the strengthening of leadership development programmes, and increased synergy between pesantren and formal educational institutions as strategies for preparing alumni who are adaptive, competitive, and relevant to the needs of education in the digital era.